All-PM Fiber Tm-Doped Laser with Two Fiber Lyot Filters Mode-Locked by CNT - Yan Ososkov; Aleksandr Khegai; Konstantin Riumkin; Aram Mkrtchyan; Yuriy Gladush; Dmitry Krasnikov; Albert Nasibulin; Mikhail Yashkov; Alexey Guryanov; Mikhail Melkumov (Photonics, 2022)
We report on the first demonstration of the Tm-doped all-PM mode-locked fiber laser with CNT used as a saturable absorber and two fiber Lyot filters embedded into the ring resonator. Using these two filters, we were able to adjust the central wavelength of laser generation to ~1855 nm as well as to obtain the required spectral width and necessary pulse duration that are required for the proposed applications. Possible issues with the method used are discussed.